Understanding Spanish Financial crises, 1850-2000: What determined their severity? - Concha Betrán; María A. Pons (European Historical Economics Society (EHES), 2013)
The objective of this paper is to study the financial crises that have occurred in Spain over the last 150 years. With this objective in mind, the paper has two main purposes. Firstly, we determine the number of crises that took place between 1850 and 2000 considering currency, banking and stock market crises and all their possible combinations and define their depth or severity using different indicators. Secondly, we consider potential factors that could explain the depth or intensity of the crises in Spain. According to our results, each financial crisis has its own particularities and it is very difficult to find common factors in the origin of the Spanish financial crises. Despite this, the current account is the variable most clearly associated with crisis intensity.
Keywords: 330